ANALYSIS OF SCIENTIFIC RESEARCH ON THE STUDY OF THE PHYSIOLOGICAL EFFECTS OF HEAVY METALS ON PLANTS, ANIMALS AND HUMAN BODY (Scientific journal of the Fergana State University, 2024)
This article presents a review of the literature devoted to the study of the mechanisms of heavy metals' effects on plant, human, and animal organisms. Nowadays, along with the development, there are many factors that threaten the life of living organisms in nature. In recent years, as a result of industrial development, the environment is polluted with various harmful substances. Especially, the presence of heavy metals among such substances means that humanity should be more aware than ever. Due to the wide range of effects of heavy metals, it has been thoroughly studied that they accumulate in various organs of organisms and cause serious changes. The literature on the mechanism of physiological effects of heavy metals was studied and relevant conclusions were drawn. In this field, not only the works of Uzbek scientists, but also the works of some scientists from all over the world were studied.